Land resource inventory database: A tool for improved farm resource management - Ravi, K. N.; S. M., Vanitha; Dupdal, Ravi; Madhu, M.; B. K., Rao (Indian Farming, 2025)
The article draws insights from monitoring and impact evaluation of Land Resource Inventory (LRI) based watershed planning process adopted to promote site-specific, scientific management of farm resources, enhance agricultural productivity in watersheds implemented under World Bankaided Sujala-III project in Karnataka state. It examines comparative overview of LRI cards and soilhealth cards generated in different programmes. Further, it highlights the benefits of integration of the soil health card with LRI development process to prevent duplication in soil sampling and data generation efforts. Upscaling the LRI generation process to other rainfed areas of the country and promoting stakeholder capacity-building with timely accessibility of digitized LRI information for both farmers and extension workers will enable relevant guidance for efficient management of farm resources.